Towards a global administrative space in environmental governance? Mapping the administrative embeddedness of international environmental secretariats - Jörgens, H.; Saerbeck, B.; Well, M.; Kolleck, N.; Goritz, Alexandra; Schuster, J. (IASIA Conference 2019, 2019)
The concept of “global administrative space” denotes the emergence of administrative structures beyond the territory of the nation state. These structures are thought to underpin processes of global governance. Against this backdrop, we argue that a global administrative space is emerging in environmental governance, which combines the development and strengthening of independent administrative capacities at the international level with an increasing integration of a broad range of governmental and non-governmental organizations at different levels of government. This administrative space constitutes a complex multi-level and multi-actor structure for the management of global environmental policies. Based on an original dataset covering issue-specific cooperation and communication flows between organizations operating in the fields of global climate and biodiversity governance, we use social network analysis to describe and analyze the structure and composition of administrative networks in the field of global environmental politics. Our exploratory study finds a relatively stable pattern of mutual interaction among international environmental bureaucracies, other international organizations, national and subnational ministries and agencies, research institutes and NGOs that can be interpreted as an indicator for the emergence of a global administrative space in environmental governance. Our paper speaks to the existing research on the European and global administrative space. In particular, it aims to respond to Johan P. Olsen’s question of how an administrative space can be recognized if one has emerged (Olsen, 2003: 506). We propose social network analysis as a potentially adequate method to respond to this challenge.